Análise das tensões biomecânicas no tecido ósseo periodontal pelo método de elementos finitos - Rocha, Milena Cerqueira da (2016)
Biomechanical behavior comprehension of teeth-periodontium system in different periodontal attachment levels is essential in the understand of periodontal occlusal load bearing capability. The finite element method has been used simulating different periodontal attachment situations and could analyze periodontal alveolar bone stress modulation by morphological changes. The aim of this study was to assess qualitative and quantitatively the stress concentration in periodontal alveolar bone in computational models simulating healthy teeth with and without attachment loss. Six 3-D models of a lower central incisor were created simulating the teeth structure, cancellous bone, cortical bone and periodontal ligament space. Each model presented a 1mm increasing distance between cement-enamel junction (CEJ) and alveolar bone crest (ABC) (1 to 6 mm) as only modification. A 100N load with 45o angle to the axial plane with bucco-lingual direction on tooth incisal edge were simulated. Each structure was considered elastic, isotropic, homogeneous, continuous and linear. Lamina Dura and alveolar bone crest findings of Minimum Principal Stress (MPS) were analyzed. Results showed an increase of MPS in surrounding bone (alveolar bone crest and lamina dura) due to periodontal attachment loss. Maximum and minimum values of MPS were concentrated on certain areas in both analyzed regions. Statistically significant differences in magnitude, distribution and variance of MPS were found between groups. Each increased millimeter in CEJ-ABC distance generated a pattern insertion area reduction of about 12%. The considered significance level was 5%. According to results obtained, attachment loss increases stress concentration in surrounding bone. Despite eventual limitations of the model, the results suggest a biomechanical changing in stress pattern, which partly explain an increasing bone resorption risk for teeth with periodontal attachment loss.